Individual Learning Reflection - Gawkasem, Jate (2014)
Fresh from completing the business plan for the management project, I can certainly conclude that it was one the most difficult write-up that I have had done throughout my professional and educational career. And despite having support from my colleague as the business plan was constructed as a group project, the amount of research and details that each individual has to acquire in order to support the validity of our assumptions and hypothesis was certainly an experience to remember. Although intensive work and effort was put into completing the business plan, there were plenty of benefits gained as the process of running such business expanded my perception towards certain factors that needed to be considered if I chose to execute this plan in the near future.